Analisis Akar Penyebab Pembunuhan dalam Masyarakat Indonesia: Perspektif Teori Anomie Durkheim - Husnul Khotimah; Kartika Dewi; Lia Karunia Lam Uli Lubis; Muhammad Daffa Adi Prayogo; Santika Virdi; Siti Umi Khoiriah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Homicide is one of the most serious crimes that threaten the security and welfare of Indonesian society. This study aims to explore the root causes of homicide in the Indonesian context by adopting the perspective of anomie theory developed by Émile Durkheim. Anomie theory highlights the role of social factors in influencing crime rates, including homicide. In Indonesia, a number of social factors can be linked to an increase in homicides, including significant economic inequality, ethnic and religious conflict, changing social norms, psychological disorders, and easy access to weapons. These factors are interrelated and influence homicide rates in Indonesia. This study aims to provide in-depth insight into the issue and explore both the impact and effective prevention strategies. It is hoped that further understanding of the root causes of homicide will assist in efforts to improve the security and well-being of Indonesian society.